Transanal total mesorectal excition (taTME): our first experience - Mikalauskas, Saulius; Kryžauskas, Marius; Jurkevičiūtė, Dignė; Pečiulytė, Vytautė; Danys, Donatas; Poškus, Tomas; Jotautas, Valdemaras; Poškus, Eligijus; Beiša, Virgilijus; Strupas, Kęstutis (Lietuvos chirurgija, 2016)
Transanal total mesorectal excision (taTME) is a new natural orifice translumenal endoscopic surgery modality combined of three rectal surgery techniques. Detailed analysis of the taTME is the object of this article. We submit the report of three taTME procedures for histologically confirmed rectal adenocarcinoma that were performed for the first time in Lithuania, Vilnius University Hospital Santariskiu Klinikos.